Spectrum of cardiac abnormalities associated with long QT in stroke survivors. Issue 10 (14th September 2005) - Wong, K Y K; McSwiggan, S; Kennedy, N S J; Wong, S Y S; Gavin, A; MacWalter, R S; Struthers, A D
Abstract : Objectives: To find out what spectrum of cardiac abnormalities are found in those stroke survivors who can be deemed to be at high cardiac risk by their having long QT. Methods: 202 patients with good recovery from a cerebrovascular event occurring at least one month previously were recruited into a prospective epidemiological study. These stroke survivors underwent a battery of cardiac investigations including 12 lead ECG, echocardiography, myocardial perfusion scanning, and heart rate variability assessment. The ECGs were digitised by a single observer blinded to the blood pressure and other investigations of the patients. The maximum heart rate corrected QT interval (QTc max) in the 12 lead ECG was derived by Bazett's formula. Results: Prolonged QTc max significantly correlated with increasing blood pressure, left ventricular mass index, and depressed heart rate variability. As the number of cardiac abnormalities increased, QTc max became more prolonged. Conclusions: Long QT is significantly associated with left ventricular mass index even after adjustment for both systolic and diastolic blood pressures. Long QT was also associated with the total cardiac disease burden. These two observations may explain why stroke survivors with long QTc max were at greater risk of cardiac death.